2018
DOI: 10.15587/1729-4061.2018.127210
|View full text |Cite
|
Sign up to set email alerts
|

Development of graphic­analytical models for the software security testing algorithm

Abstract: Визначено, що існує ряд специфічних особливостей, пов'язаних з можливістю негативних маніпуляцій програмним продуктом. Розроблено графоаналітичну модель алгоритму тестування безпеки програмного забезпечення. Отримано співвідношення для розрахунку статистичних характеристик випадкового часу виконання даного алгоритму. Модель можна використовувати для дослідження етапів тестування безпеки програмного забезпечення. Застосування моделі дозволить знизити уразливість IT-проекту в цілому Ключові слова: тестування без… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
10
0
6
Order By: Relevance
“…The review of the literature [4][5][6][7][8][9][10][11][12] showed that for a number of special cases, the final results of the study taking into account possible limitations are presented. So, in [4][5][6], comprehensive results are obtained for the case when a random process determining transitions from one state to another is formalized by the exponential distribution law.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The review of the literature [4][5][6][7][8][9][10][11][12] showed that for a number of special cases, the final results of the study taking into account possible limitations are presented. So, in [4][5][6], comprehensive results are obtained for the case when a random process determining transitions from one state to another is formalized by the exponential distribution law.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Особливої уваги заслуговують дослідження направлені на побудову операцій криптоперетворення які забезпечують максимальну невизначеність результатів шифрування [7][8][9][10][11][12].…”
Section: вступunclassified
“…Особливості реалізації кожного методу синтезу операцій визначається особливостями синтезу операцій базової групи. Технічній реалізації однооперандних операцій присвячено ряд робіт [7][8][9][10][11][12]. Особливої уваги заслуговують дослідження присвячені та синтезу апаратних засобів генерації однооперандних операцій [13,14].…”
Section: вступunclassified